Hedging market exposures identifying and managing market risks - Bychuk, Oleg V., 1963- (Wiley finance series., 2011)
"Identify and understand the risks facing your portfolio, how to quantify them, and the best tools to hedge them This book scrutinizes the various risks confronting a portfolio, equips the reader with the tools necessary to identify and understand these risks, and discusses the best ways to hedge them. The book does not require a specialized mathematical foundation, and so will appeal to both the generalist and specialist alike. For the generalist, who may not have a deep knowledge of mathematics, the book illustrates, through the copious use of examples, how to identify risks that can sometimes be hidden, and provides practical examples of quantifying and hedging exposures. For the specialist, the authors provide a detailed discussion of the mathematical foundations of risk management, and draw on their experience of hedging complex multi-asset class portfolios, providing practical advice and insights. Provides a clear description of the risks faced by managers with equity, fixed income, commodity, credit and foreign exchange exposures Elaborates methods of quantifying these risks Discusses the various tools available for hedging, and how to choose optimal hedging instruments Illuminates hidden risks such as counterparty, operational, human behavior and model risks, and expounds the importance and instability of model assumptions, such as market correlations, and their attendant dangers Explains in clear yet effective terms the language of quantitative finance and enables a non-quantitative investment professional to communicate effectively with professional risk managers, "quants", clients and others Providing thorough coverage of asset modeling, hedging principles, hedging instruments, and practical portfolio management, Hedging Market Exposures helps portfolio managers, bankers, transactors and finance and accounting executives understand the risks their business faces and the ways to quantify and control them"--